The Effect of Learning Methods on Student Participation and Achievement in Chemistry Education - Sinaga, Dewi Agustina; Harahap, Iza; Marbun, Nova Fajria; Ravisa; Sazkia; Samosir, Rafidah Almira (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
This study analyzes the role of various instructional methods in enhancing student engagement and academic achievement in chemistry learning. The research employed a qualitative descriptive approach using a literature review design that examined findings from peer-reviewed journal articles, classroom action research, and educational reports. The synthesis of the reviewed studies indicates that student-centered instructional methods, particularly Project-Based Learning (PBL) and collaborative learning, consistently lead to higher levels of participation, conceptual comprehension, and overall learning outcomes. Meanwhile, teacher-centered lecture methods tend to result in lower engagement and weaker retention. The review also shows that combining multiple instructional strategies allows teachers to respond more effectively to differences in learners’ needs, characteristics, and learning objectives. The research concludes that blended instructional approaches that integrate project-based, collaborative, and reflective learning activities create more interactive and meaningful chemistry learning environments, while also supporting the development of essential twenty-first-century competencies.